2006
DOI: 10.1074/jbc.m511884200
|View full text |Cite
|
Sign up to set email alerts
|

The Latent Membrane Protein 1 of Epstein-Barr Virus (EBV) Primes EBV Latency Cells for Type I Interferon Production

Abstract: Epstein-Barr virus (EBV)3 is a human ␥ herpesvirus and is an important cause of lymphomas in patients with advanced human immunodeficiency virus infection or AIDS and in severely immunocompromised people, especially organ transplant recipients. Also, EBV infection is associated with the development of nasopharyngeal carcinoma and Burkitt's lymphoma (BL) (1, 2).The biologic hallmark of EBV-cell interaction is latency. Three types of latency have been described, each having its own distinct pattern of gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 71 publications
1
44
1
Order By: Relevance
“…EBV LMP-1 has been shown to suppress EBV reactivation triggered by either anti-immunoglobulin M or TPA (3,63). In addition, we have shown that LMP-1 is an antiviral protein (87,90). These published results suggest that LMP-1 might inhibit the lytic replication of KSHV.…”
Section: Ebv Inhibits Lytic Replication Of Kshvmentioning
confidence: 55%
“…EBV LMP-1 has been shown to suppress EBV reactivation triggered by either anti-immunoglobulin M or TPA (3,63). In addition, we have shown that LMP-1 is an antiviral protein (87,90). These published results suggest that LMP-1 might inhibit the lytic replication of KSHV.…”
Section: Ebv Inhibits Lytic Replication Of Kshvmentioning
confidence: 55%
“…For example, although V protein of parainfluenza 5 antagonizes IFN response by degrading STAT1, appropriate IFNs may change the pattern of viral transcription and protein synthesis, and thus facilitate the establishment of persistent infections (52)(53)(54). SM protein of EBV during the lytic cycle inhibits protein kinase R activation, whereas EBV LMP-1 protein can prime EBV latency cells for IFN production to establish the viral latency (55)(56)(57). Recent studies have demonstrated that HBoV can establish persistent infection in host cells by forming episomes (58).…”
Section: Discussionmentioning
confidence: 99%
“…Since the stimuli are diverse, the mechanisms that govern the activity of IRF7 are likely to be complex and are important to understand. We have However, IRF7's role may be in priming of latently EBVinfected cells by LMP1 for IFN production, the effect of which is to inhibit lytic EBV replication and superinfection by other viruses and thus to avert disruption of latency (42). Maintenance of latency is important for viral persistence because EBV, particularly the lytic antigens, generates robust cytotoxic-T-cell responses (30).…”
Section: Discussionmentioning
confidence: 99%
“…IRF7 is necessary for LMP1-induced up-regulation of Tap-2 expression (45) and has been implicated in LMP1-mediated priming of EBV latently infected cells for production of type I IFN (42). In this study, we examine LMP1 signaling events that lead to the activation of IRF7.…”
mentioning
confidence: 99%